Immersion and Beyond: A critical approach to understanding the aesthetic potential of 3D audio (International Journal on Stereo & Immersive Media, 2019)
Since around one decade, the word “immersion” has become one of the major terms relating to current developments in digital media. Being able to (re-)create the experience of being surrounded by and immersed in sensory impressions is widely considered as a main characteristic of nowaday’s digital technologies, as for example in games, in 360° film or in 3D audio. As in 3D audio, immersion’s aesthetic strength is mainly assigned to cohesiveness as well as to its capability to create an “as if” experience. By this it is coming very close to the experience of reality, and is touching, if not transgressing the boundaries to Virtual Reality.Concerning sound and audiomedia, there is, however, an interesting history of critical approach, when it comes to illusionism and realism made possible and enhanced by new technologies. This paper will not only point out critical aspects of immersion as a goal for media experience in general, but show artistic methods and strategies, by which the critique can be made fruitful, expanding 3D-audio’s aesthetic potential beyond the limitations of the merely obvious.